Treatment of relapsing autoimmune pancreatitis with immunomodulators and rituximab: the Mayo Clinic experience. Issue 11 (30th August 2012) - Hart, Phil A; Topazian, Mark D; Witzig, Thomas E; Clain, Jonathan E; Gleeson, Ferga C; Klebig, Robin R; Levy, Michael J; Pearson, Randall K; Petersen, Bret T; Smyrk, Thomas C; Sugumar, Aravind; Takahashi, Naoki; et al.
Abstract : Background: There is a paucity of data on long-term management of type 1 autoimmune pancreatitis (AIP), a relapsing steroid-responsive disorder. Objective: We describe our experience with treatment of relapses and maintenance of remission using steroid-sparing immunomodulators (IMs) and induction of remission using rituximab (RTX). Methods: We obtained details of disease relapse and treatment in 116 type 1 AIP patients from clinic visits, medical records and telephone interviews. We compared relapse free survival in those treated with IMs versus those treated with steroids alone, assessed patients' response to RTX, and identified treatment-related complications. Results: During a median follow-up of 47 months, 52/116 AIP patients experienced 76 relapse episodes. The first relapse was treated with another course of steroids in 24 patients, and with steroids plus IM in another 27 patients; subsequent relapse-free survival until a second relapse was similar in the two groups (p=0.23). 38 patients received an IM for >2 months; failure or intolerance of IM therapy occurred in 17 (45%). 12 patients with steroid or IM intolerance/resistance were treated with RTX, an antiCD20 antibody; 10 (83%) experienced complete remission and had no relapses while on maintenance therapy. Treatment-limiting side effects related to RTX were uncommon. Conclusions: In type 1 AIP relapses are common. Relapse-free survival is similar in those treated with steroids plus IM compared to those treated with steroids alone. Nearly half the patients on IMs will relapse during treatment. RTX is effective in the treatment of both IM resistant and steroid intolerant patients.